Validity of LKPD based constructivism approachment - Dini Fajria Trisna; Hendra Syarifuddin; Ratnawulan Ratnawulan (Fakultas Ilmu Pendidikan UNP)
Problem solving ability is one of the mathematical abilities that are important in the success of students. But the fact remains low problem solving ability. One approach that can develop problem solving ability is constructivism approachment. The constructivism approach is one of the learning approaches which can trigger students to build their own knowledge and help students find their own mathematical principles or procedures. LKPD is one important component in learning. LKPD used by teachers not specifically describe the learning process, as well as yet to be seen developing students' problem solving abilities. This study aims to determine the validity of LKPD based on constructivism approach. This research is a development research by using Plomp model which consists of preliminary research, development stage and assessment phase. The results of data analysis show that the developed LKPD has been valid with the validity index of 0,848 so it can be used to increase problem solving student ability.